Mental health and learning achievement during the COVID-19 outbreak: A lesson from online learning among Indonesian college students - M. A. Rafsanjani; P. A. Wijaya; A. Baskara; H. D. Wahyudi (Russian State Vocational Pedagogical University, 2023)
Introduction. All educational institutions have to adjust the learning format, from face-to-face to online learning, due to the COVID-19 outbreak. The sudden shifting of the learning format raised several problems for the students and led to mental health issues.Aim. This study aimed to examine the effect of mental health on students' learning achievement during online learning in the COVID-19 outbreak.Methodology and research methods. This study used partial least square structural equation modelling (PLS-SEM) to examine the research model on a random sample of 518 respondents.Results. The online learning activities during the COVID-19 outbreak have developed mental health issues, such as anxiety and depression. Furthermore, the results indicated that mental health negatively predicted the students' learning achievement.Scientific novelty. This study reveals certain situations and conditions that could be affected to the student's mental health and learning achievement.Practical significance. This study can be useful to the government as policymakers and administrators of the university as current research provides a critical understanding of the online learning influence on mental health and learning achievements of students. The government and administrators of the university should consider the right policy for learning activities during the COVID-19 outbreak. The government and administrators of the university also should provide student services to minimise the mental health issues among college students during online learning activities.